A MODEL OF EMPOWERMENT OF A POOR COMMUNITY BASED ON SOCIAL RESPONSIBILITY WITH ISLAMIC VALUES - Agus Wahyu Triatmo; Ravik Karsidi; Drajat Tri Kartono; Suwarto Suwarto (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2018)
Empowering the poor is the responsibility of all members of society, not just the government. Muslims, as the majority in Indonesia, should play a significant role in poverty alleviation. Zakat, infak and sedekah (ZIS), in the teachings of Islam, is not just worship because, if managed properly, it can be a solution to poverty. To date, the management of ZIS as a mechanism for change in society has not been optimal due to various factors, one of which is a poor management model. Therefore, this article presents a model of empowerment of the poor based on social responsibility with the integration of Islamic values. This article is based on research conducted at Yayasan Solo Peduli Umat. The research data are obtained from the managers of Solo Peduli, beneficiaries and other parties involved. The results of this study indicate that the integration of Islamic values with the concept of social responsibility can maximize the empowerment of the poor. An empowerment model is created to increase the number of entrepreneurs who diligently worship and have noble morality (akhlaqul karimah), increase the independence and welfare of the poor, ensure the continuity of network-based businesses between musthik and muzaki/ donatur, and provide sustainable donations to be used as capital for social transformation